Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.biocel.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Dynein binds and stimulates axonal motility of the endosome adaptor and NEEP21 family member, calcyon

Abstract: The neuron-enriched, endosomal protein Calcyon (Caly) regulates endocytosis and vesicle sorting, and is important for synaptic plasticity and brain development. In the current investigation of Caly interacting proteins in brain, the microtubule retrograde motor subunit, cytoplasmic dynein 1 heavy chain (DYNC1H), and microtubule structural proteins, α and β tubulin, were identified as Caly associated proteins by MALDI-ToF/ToF. Direct interaction of the Caly-C terminus with dynein and tubulin was further confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…We predicted that if endogenous Caly stimulates dynein, then Caly RNAi should reduce retrograde movement of LysoTracker-labeled vesicles. Knockdown (KD) of endogenous Caly in axons was confirmed by staining with an antibody to Caly ( Shi et al , 2017 ), although the protein was still present in cell bodies after 48 h when time-lapse recordings were made ( Figure 1A ). LysoTracker-labeled organelles were less numerous in CalyKD axons ( Figure 1, B and C ).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…We predicted that if endogenous Caly stimulates dynein, then Caly RNAi should reduce retrograde movement of LysoTracker-labeled vesicles. Knockdown (KD) of endogenous Caly in axons was confirmed by staining with an antibody to Caly ( Shi et al , 2017 ), although the protein was still present in cell bodies after 48 h when time-lapse recordings were made ( Figure 1A ). LysoTracker-labeled organelles were less numerous in CalyKD axons ( Figure 1, B and C ).…”
Section: Resultsmentioning
confidence: 94%
“…Our previous studies showed that Caly directly interacts with DIC ( Shi et al , 2017 ). In the present study, we explored whether Caly could also play a role in axonal transport and specifically sought to test the hypothesis that Caly regulates dynein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have linked synapins to the memory process and aging-related memory impairments in mammals [ 81 , 82 , 83 ]. Caly is known as a calcyon neuron specific vesicular protein that controls excitatory synaptic neurotransmission, vesical sorting, and synapse stability [ 84 , 85 ]. Inpp5f is predicted to be involved in protein transport and vesicle-mediated transport.…”
Section: Resultsmentioning
confidence: 99%
“…3C and fig. S3B) related to neuron morphogenesis (24)(25)(26)(27), and these genes may also be essential for the morphogenesis of SubC-PyNs.…”
Section: Characterization Of Subtype-specific Foxg1-driven Transcript...mentioning
confidence: 99%